2-2(1+8x)=8x+7(-4-4x)

Simple and best practice solution for 2-2(1+8x)=8x+7(-4-4x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2-2(1+8x)=8x+7(-4-4x) equation:



2-2(1+8x)=8x+7(-4-4x)
We move all terms to the left:
2-2(1+8x)-(8x+7(-4-4x))=0
We add all the numbers together, and all the variables
-2(8x+1)-(8x+7(-4x-4))+2=0
We multiply parentheses
-16x-(8x+7(-4x-4))-2+2=0
We calculate terms in parentheses: -(8x+7(-4x-4)), so:
8x+7(-4x-4)
We multiply parentheses
8x-28x-28
We add all the numbers together, and all the variables
-20x-28
Back to the equation:
-(-20x-28)
We add all the numbers together, and all the variables
-16x-(-20x-28)=0
We get rid of parentheses
-16x+20x+28=0
We add all the numbers together, and all the variables
4x+28=0
We move all terms containing x to the left, all other terms to the right
4x=-28
x=-28/4
x=-7

See similar equations:

| 12x+20=4x/3 | | 4x-25=-3 | | 11−2f=5 | | x^2+11x-64=90 | | 200000=(20*0.6x)+(24*0.4x)-6280000 | | -6p-8(4p+)=98 | | 8p+2P=60 | | -7u-9+2(3u+7)=-2(u+2) | | 30x^2=15x | | 2-2(1+8x=8x+7(-4-4x) | | -7-9+6u+14=-2u+4 | | x+76+43=180 | | 5+3q=6+2q= | | -3=c-7c= | | 7(6g+3)+40=126 | | 7x-+4=24 | | x2-21x=-110 | | 20-2k=2 | | 2-2k=-4 | | 4f-28=100 | | x+90+53=180 | | -3.5x=54.60 | | 27+0.10x=23+0.15x | | 5z-10=-15 | | 25x=156 | | 24=9x+4-5x= | | 2x=5.9 | | 7(2n-8)=8+5(n-2) | | 3(x-2)+20=-4 | | 3q-3=-9 | | -15u-2u+29=5u-27 | | k-90=10 |

Equations solver categories